Does the Clean Development Mechanism have a viable future? - Cathrine Hagem; Bjart Holtsmark (Statistics Norway, Research Department, 2009)
The developed countries can meet part of their Kyoto commitments by investing in emission-reducing projects in developing countries (the Clean Development Mechanism, CDM). Since the developing countries have so far not been willing to accept binding emission commitments, the CDM has been the only mechanism available for ensuring emission-abatement measures in developing countries. We argue that the CDM is not an efficient tool for achieving deep cuts in global emissions and conclude that maintaining the CDM as an option for developing countries may in itself be a serious obstacle to more binding participation by these countries.
Keywords: Q54; Q56; 330; Clean development mechanism; climate agreement; emissions trading; emissions reductions.